Pelayanan Program Pendidikan Kejar Paket C Di PKBM Anugrah Bangsa Semarang: Kajian Penilaian Kualitas Pelayanan - Anisya, Thyo Rizky; Shofwan, Imam (Universitas Pahlawan Tuanku Tambusai, 2024)
Non-formal education plays a fundamental role in transforming access to education for communities hindered by conventional formal education systems. This study aims to comprehensively explore the service quality of the Package C Education Program at PKBM Anugrah Bangsa Semarang, with a primary focus on analyzing service dimensions, identifying barriers, and mapping strategies to improve service quality. Using a qualitative methodology approach, the research employs a field study design with data collection methods through source triangulation, including in-depth observation, comprehensive interviews with various stakeholders (managers, tutors, and learners), and systematic documentation. Data analysis is conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The findings reveal that the service quality of PKBM Anugrah Bangsa shows positive achievements with several excellent aspects. The professionalism of the staff is reflected in their neat appearance, effective communication, and responsiveness to customer needs. However, the study also identifies several significant challenges, including limitations in technological infrastructure, suboptimal distribution of responsibilities, and coordination mechanisms that require improvement. The research recommends a series of strategic interventions, including the continuous development of infrastructure, strengthening internal coordination, implementing a responsive complaint management system, and enhancing external communication through digital platforms to improve accessibility and transparency in non-formal education services.